Reaching and Teaching All Instrumental Music Students - Mixon, Kevin (Rowman & Littlefield Publishers, 2011)
Reaching and Teaching All Instrumental Music Students draws from credible research and established approaches to offer practical applications for the variety of music classrooms teachers face today, many of which are not ideal. Kevin Mixon shares successful techniques for recruiting and retention, garnering program support, teaching for diverse learning styles and exceptional students, classroom management, and teaching notation, composition, and improvisation. This expanded second edition adds practical advice on reading rhythm notation, teacher feedback, home visits, community building, and establishing positive relationships_with even the most challenging students. Mixon demonstrates that fostering respect and going the extra mile are rewarding for students, parents, and teachers alike.